A non‐isolated modified ultra high step‐up quadratic boost converter with classical voltage doubler circuit - Abdullah Al Mahbub Emon; Mahzabin Tabassum; Nafis Subhani; Kishore Bingi (The Journal of Engineering)
Abstract This paper proposes a modified ultra‐high gain DC–DC boost converter. The proposed converter has improved the performance of the conventional converter by reducing the total number of components (1 Capacitor and 1 Inductor) in the design structure. In addition, the continuous input current and high voltage gain features are retained in the proposed structure. The steady‐state modelling including the operating principles and the stress calculation along with the cost analysis of the components have been illustrated. The comparative performance analysis has been carried out to clarify the competitiveness of the proposed converter against the recent models. The proposed model has been simulated in Matlab/Simulink software and further, a 100 W laboratory prototype has been built to evaluate the performance of the proposed converter. The peak efficiency received was 90.5% while delivering 100 W power from the source. The results from the experiments have aligned well with the outcomes of the simulation and verify the correctness of the proposed converter.